Acute Effect of Exergames on Children's Mood States during Physical Education Classes - Correia C.K.* (2019)
© 2019, Mary Ann Liebert, Inc.Objective: We aimed to confirm whether the practice of exergames produces an effect on children's mood states during school physical education (PE) classes. Materials and Methods: The children were allocated to experimental group (EG) and control group (CG). The EG performed exergames during PE classes, and the CG attended regular school PE classes. The Brunel Mood Scale, which evaluates six mood dimensions (tension, mental confusion, anger, vigor, depression, and fatigue), was used to assess the children's moods before (pre) and immediately after the third lesson (acute effect). Results: The practice of exergames during PE classes produced an acute effect on children's moods. The results indicated that playing exergames helped to increase vigor (P < 0.01; effect size [ES]: 0.50; confidence interval [CI]: 0.16-0.84) and fatigue (P < 0.01; ES: 0.50; CI: 0.16-0.84). Conclusion: Three exergame sessions produced an acute effect and improved children's moods during school PE classes. More research is needed to evaluate the long-term effect of exergames on children and adolescents.